Development of Alternaria blight resistant lines through interspecific hybridization between Indian mustard (Brassica juncea L.) and white mustard (Brassica alba) through embryo rescue - Ram C Yadav; Dhiraj Singh; Asha Rani; Ajit Singh Rathi; Rajesh Arya; Rajinder Singh; Neelam R Yadav; Amit Singh; Ramavtar (Journal of Oilseed Brassica, 2026)
Wide hybridization is an important technique for incorporation of desirable characters among related species of plants.In the present study, interspecific hybridization was carried out through in vitro culture of ovules from the crossesbetween Brassica juncea (cv. RH30, RH8812, RH270 and RH345) and B. alba for purpose of transferring Alternaria blightresistance from B. alba to B. juncea. Ovules were excised from siliquae and cultured on seven different MS modifiedmedia. In all crosses, the hybrid siliquae were shorter in length than their parent plants due to interspecific hybridizationbarriers. Pod setting in hybrid plants ranged from 39 to 48% and number of ovules per pod were also very few. Bestgermination response was observed in ovules used from 20 DAP on basal medium supplemented with Kin (2.5 mg/l) andCH (0.5 g/l) (for cv. RH30 x B. alba) and MS + BAP (2.5 mg/l) + CH (0.5 mg/l) (for other crosses). Six rooting media weretried for root formation in regenerated shoots. Maximum rooting response was on MS medium supplemented with IAA(0.5 mg/l) in all hybrids. The regenerated hybrid plants were transferred to a mixture of sand: soil in 1:1 ratio in pots andabout 70 percent hybrid plants for all the crosses were survived. Successful hybrid plants were grown in field upto F7generations. Advanced generation progenies were also successfully confirmed using molecular marker analyses forAlternaria blight resistance character. In advanced generation, the hybrid plant’s characteristics were comparable totheir Indian mustard parent plants and they were highly resistant to Alternaria blight disease.